THE EFFECTIVENESS OF SCANNING TECHNIQUE ON READING RECOUNT TEXT FOR EIGHTH GRADE STUDENT OF MTS NURUL HASANAH PENGAWU - Mufidah, Nur; Kuliahana, Ana; Zuhra, Zuhra (Datokarama English Education Journal, 2024)
This study investigated the effectiveness of the scanning technique in improving reading comprehension of recount texts among eighth-grade students at Madrasah Tsanawiyah Nurul Hasanah Pengawu. The primary objective was to determine whether the scanning technique enhanced students' ability to comprehend recount texts. A quantitative approach was adopted, utilizing a quasi-experimental design. The research involved 35 eighth-grade students selected through purposive sampling based on specific criteria, with class VIIIB assigned as the experimental group and class VIIIA as the control group. Before the intervention, students struggled with understanding recount texts. However, after the experimental group received treatment using the scanning technique, their performance improved significantly, as evidenced by an increase in their average scores from 45.33 in the pre-test to 76.94 in the post-test. These findings indicated that the scanning technique was an effective method for enhancing reading comprehension of recount texts in this context.